The Future Delivered: Rethinking Last Mile in the Age of Instant Gratification - Sharma, Arjun (ExcelingTech, 2024)
This study explains the problems faced in last mile delivery (LMD) and suggests innovative solutions for them. The demand for home delivery services for delivering small package to the customers’ doorsteps has expanded rapidly due to the exponential growth of online shopping. Last mile delivery has now become a key success factor for any business, thanks to the rapid development of information and communication technology (ICT), e-commerce and the COVID-19 pandemic. Final-mile delivery on the very same day as placing the order for a product, has turned out to be a critical success factor for businesses, since modern-day customers have grown new habits and hence new expectations - the expectation of expedited demand fulfillment through door-step delivery of the products they shop online. Though the costliest leg of the supply chain, LMD will always be what creates the competitive edge for the e-commerce. It is necessary for sustenance and success.